Notes on Leuctra signifera Kempny, 1899 and Leuctra austriaca Aubert, 1954 (Plecoptera: Leuctridae), with the description of a new species - Reding, Jean-Paul G.; Vinçon, Gilles; Graf, Wolfram (Zootaxa, 2023)
Leuctra signifera Kempny, 1899 and Leuctra austriaca Aubert, 1954 are re-described and their taxonomical status is discussed. New country records are reported for L. austriaca from Hungary and L. signifera from Italy, Slovenia, and Hungary. A new species, Leuctra papukensis sp. n., from Croatia, is described and illustrated. The subspecies Leuctra signifera jahorinensis Kaćanski, 1972 is raised to species level.